2023
DOI: 10.1101/2023.06.20.543103
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing Adeno-Associated Virus Capsids with both Denaturing and Intact Analysis Methods

Abstract: Adeno-associated virus (AAV) capsids are among the leading gene delivery platforms used to treat a vast array of human diseases and conditions. AAVs exist in a variety of serotypes due to differences in viral protein sequences, with distinct serotypes targeting specific cells and tissues. As the utility of AAVs in gene therapy increases, ensuring their specific composition is imperative for correct targeting and gene delivery. From a quality control perspective, current analytical tools are limited in their se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…209,210,705−707 The coming years will be exciting times for CDMS and intact protein analysis, especially as it has (so far) been commercialized as Direct Mass Technology on the newest generation Q-Orbitrap platforms. 207,208,704,708 Structural Proteomics. Deriving the protein structure from MS data has long been a goal of the proteomics community, and modern instrumentation has helped make it a reality.…”
Section: Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…209,210,705−707 The coming years will be exciting times for CDMS and intact protein analysis, especially as it has (so far) been commercialized as Direct Mass Technology on the newest generation Q-Orbitrap platforms. 207,208,704,708 Structural Proteomics. Deriving the protein structure from MS data has long been a goal of the proteomics community, and modern instrumentation has helped make it a reality.…”
Section: Proteomicsmentioning
confidence: 99%
“…CDMS is a single-ion detection strategy used to simultaneously measure charge (via induction of an image current) and m/z (traditionally via TOF). , In this way, CDMS provides mass measurements of large biomolecules (beyond MDa masses) that typically cannot be assigned a charge state in ESI-FTMS because resolution is not sufficient for isotopic resolution . The Kelleher and Heck groups recently demonstrated that individual ion CDMS measurements can be made within commercial Orbitrap systems rather than requiring custom MS hardware often used for CDMS. ,, Orbitrap CDMS is particularly promising for DNA-containing viral capsids, glycoproteins, protein complexes, and amyloid protein aggregates, and it also boosts performance of top-down MS via improvements to sensitivity and protein sequence coverage. ,, The coming years will be exciting times for CDMS and intact protein analysis, especially as it has (so far) been commercialized as Direct Mass Technology on the newest generation Q-Orbitrap platforms. ,,, …”
Section: Evolution Of Experimental Design In Proteomicsmentioning
confidence: 99%
“…[207][208][209][210]704,705 Orbitrap CDMS is particularly promising for DNA-containing viral capsids, glycoproteins, protein complexes, and amyloid protein aggregates, and it also boosts performance of top-down MS via improvements to sensitivity and protein sequence coverage. 209,210,[705][706][707] The coming years will be exciting times for CDMS and intact protein analysis, especially as it has (so far) been commercialized as Direct Mass Technology on the newest generation Q-Orbitrap platforms. 207,208,704,708 Structural proteomics Deriving protein structure from MS data has long been a goal of the proteomics community, and modern instrumentation has helped make it a reality.…”
Section: Top-down Proteomicsmentioning
confidence: 99%
“…[196][197][198][199]677,678 Orbitrap CDMS is particularly promising for DNA-containing viral capsids, glycoproteins, protein complexes, and amyloid protein aggregates, and it also boosts performance of top-down MS via improvements to sensitivity and protein sequence coverage. 198,199,[678][679][680] The coming years will be exciting times for CDMS and intact protein analysis, especially as it has (so far) been commercialized as Direct Mass Technology on the newest generation Q-Orbitrap platforms. 196,197,677,681 Structural proteomics Deriving protein structure from MS data has long been a goal of the proteomics community, and modern instrumentation has helped make it a reality.…”
Section: Top-down Proteomicsmentioning
confidence: 99%
“…198,199,[678][679][680] The coming years will be exciting times for CDMS and intact protein analysis, especially as it has (so far) been commercialized as Direct Mass Technology on the newest generation Q-Orbitrap platforms. 196,197,677,681 Structural proteomics Deriving protein structure from MS data has long been a goal of the proteomics community, and modern instrumentation has helped make it a reality. From the intact protein angle, native proteomics relies on non-denaturing solvents and ESI to study protein structure in the gas-phase.…”
Section: Top-down Proteomicsmentioning
confidence: 99%